Secondary school-university partnerships foster STEMM interest and self-agency in rural students - Rivera, Seema; Kavanagh, Kathleen; DeWaters, Jan; Ramsdell, Mike; Burkhalter, Leigha; Johns, Lennart; Taylor, Nicole; Smith, Megan; Beldock, Lisa (Frontiers in Education, 2025)
IntroductionRural STEMM education faces significant challenges, including limited access to high-quality STEMM experiences and resources. University-K12 partnerships can address these challenges by providing opportunities for students and teachers to engage in authentic STEMM activities, build relationships with STEMM professionals, develop critical thinking and problem-solving skills, and grow professionally. This paper explores the unique assets and challenges of such partnerships in a rural, geographically isolated region of Northeastern United States.MethodsWe examine several successful STEMM programs directed by a small university through a qualitative exploratory approach. These programs include a neuroscience program, place-based environmental outreach, a student space program, and a science and technology entry program.Results and discussionThrough an analysis of reflections from teacher partners and program leaders, prominent themes emerge and critical factors are identified that contribute to success. A key finding is that teachers naturally emerge as cultural navigators who provide vital support and guidance to all stakeholders in a rural STEM network resulting in a range of positive outcomes.